Analysis of Coffee Shop Business Strategy in Bandar Lampung - Ilham Arifin; Ayi Ahadiat (PT FORMOSA CENDEKIA GLOBAL, 2023)
MSMEs boost Indonesia's economy. MSMEs create jobs and reduce poverty in Indonesia, accounting for 56% of business investment and 97% of household work. The number of coffee shops indicates market interest in them. Coffee shops are now used for studying, meeting, and hanging out with friends. Teenagers visit Bandar Lampung City's MSME businesses. Shop and cafe owners benefit from the market segmentation of young people. Even though young people and teenagers love it, a coffee shop must innovate and grow to survive because so many businesses can copy it. This study used quantitative and descriptive qualitative methods. This method collects, analyzes, and interprets data. This chapter's matching and decision stage matrices use EFE, IFE, QSPM data. Early in strategy formulation, the input tool measures subjectivity. The strategist can better generate, prioritize, evaluate, and choose strategies in the Quantitative Strategic Planning matrix by making minor decisions about the relative importance of external and internal factors in the input matrix